2017
DOI: 10.21273/horttech03648-16
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Product Label for Electric Lamps Used in the Plant Sciences

Abstract: Electric lamps are widely used to supplement sunlight (supplemental lighting) and daylength extension (photoperiodic lighting) for the production of horticultural crops in greenhouses and controlled environments. Recent advances in light-emitting diode (LED) technology now provide the horticultural industry with multiple lighting options. However, growers are unable to compare technologies and LED options because of insufficient data on lamp performance metrics. Here, we propose a standardized product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
0
20
1
Order By: Relevance
“…These results suggest that PE is likely not a good predictor of EUE in lettuce production. It is important to note that our results are specific to lettuce and differ from previous research that generally suggested using PE for LEDfixture selection for many species (Both et al, 2017;Nelson and Bugbee, 2014;Park and Runkle, 2018). In contrast to PE, a strong relation was observed between EUE and PE R (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…These results suggest that PE is likely not a good predictor of EUE in lettuce production. It is important to note that our results are specific to lettuce and differ from previous research that generally suggested using PE for LEDfixture selection for many species (Both et al, 2017;Nelson and Bugbee, 2014;Park and Runkle, 2018). In contrast to PE, a strong relation was observed between EUE and PE R (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Manufacturers of LED fixtures commonly use PE to characterize light fixtures (Both et al, 2017;Nelson and Bugbee, 2014;Park and Runkle, 2018). Greater PE values are associated with lower energy costs of producing artificial light (Kubota et al, 2016) and can thereby increase EUE (Park and Runkle, 2018).…”
mentioning
confidence: 99%
“…The averaged spectral curve was normalized and the values divided into intervals of 100 nm. Since these lamps are intended for plant growth, some of the most relevant values for this purpose were calculated and displayed similarly to how it was suggested by Both et al (2017). One of these values is the photosynthetic photon flux density (PPFD) measured in μmol m −2 s −1 under the PAR region (400-700 nm).…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…Examples include photosynthetically active radiation (PAR) efficacy [6], the ability to target specific wavebands/spectra of light, finer control over light intensity and periodicity of lighting [7], and a lower heat load produced in the direction of the light allowing them to be placed closer to a crop or operated during warm ambient conditions [5,8]. When comparing potential for energy savings in LED over HPS lights the PAR efficacy, light output per unit electricity (units: µmol/j) is used [9]. However, PAR efficacy only tells us about fixture performance and does not account for plant performance under a lighting source.…”
Section: Introductionmentioning
confidence: 99%